Development of a finite element model to study the torsional fracture strength of an analogue tibia with bicortical holes. (1st January 2013) - Reuter, Kimberly; Chong, Alexander; Madhavan, Viswanathan; Wooley, Paul H.; Virginia, Mark; Lankarani, Hamid M.
Fractured bones are often stabilised with orthopaedic fracture plates and screws until healed. If the plates and screws are removed, the vacant screw holes introduce a potential site for re-fracture. This study is aimed at simulating a laboratory torsional fracture test of a composite analogue tibia with vacant screw holes using a finite element (FE) model. This FE model is set up the same as the experimental torsion test, with a section from the distal portion of the tibia. The FE model contains over 35k second-order brick elements and nearly 165k nodes. It utilises an isotropic linear elastic material law with material properties obtained from the analogue tibia manufacturer. Comparisons between the experimental model and the FE model consider the fracture torque, fracture angle, and specific torsional stiffness. Stress contours of the FE model are compared to the fracture path of the experimental model. The FE model predicts the fracture location and a fracture torque within the standard deviation of that determined experimentally.